Immunolocalization of fibroblast growth factor-2 (FGF-2) in the developing root of the murine tooth - Madan, Anil, Kumar. (My University, 2004)
Classical epithelio-mesenchymal interactions are said to result in root development. These interactions may be regulated by a number of growth factors. Fibroblast growth factors (FGF’s), members of a highly conserved family of polypeptides, the heparin binding growth factors (HBGF’s) are known to play a crucial role during the development of certain vertebrate organs, including the tooth. Previously, FGF-2, 3, 4, and 8 have been shown to play a role in crown development. The aim of this study was therefore to elucidate the spatial and temporal expression of FGF-2 in the developing root. Parasagittal sections of the maxillary and mandibular arches of six age groups of post-natal mice (days 9, 10, 12, 16, 20 and 24) were cut and the developing roots of the incisor and molar teeth identified. Immunocytochemistry utilizing anti-FGF-2 was performed on sections of teeth from all stages using the strept-avidin biotin technique. Appropriate positive, negative and absorption controls were performed to ensure the specificity of the antibody. FGF-2 was immunolocalized in the cytoplasm and nuclei of the odontoblasts, fibroblasts of the periodontal ligament and pulp chamber, as well as in the osteoblasts surrounding developing bone at all the stages examined. Intense staining for FGF-2 was observed in differentiating odontoblasts at the apical end and the furcation zone of the developing root. FGF-2 localization was also observed in the cytoplasm of the ameloblasts on days 9, 10 and 12 and in cementoblasts on day 16, 20 and 24. The spatio-temporal expression pattern of FGF-2 in the developing mouse tooth root suggests that FGF-2 with other signaling molecules previously reported such as bone morphogenetic proteins-2, 3 and 7 (BMP-2, 3 and 7) participate in the signaling network during the tooth root development.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the Degree of Master of Science (Medicine)
Keywords: Fibroblast Growth Factor 2; Tooth; Odontogenesis